Isobaric vapour-liquid equilibria and physical properties for isopropyl acetate+isopropanol+1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide mixtures - Andreatta, Alfonsina Ester (2011)
Experimental densities, refractive indices and dynamic viscosities of binary and ternary mixtures of isopropyl acetate, isopropanol and 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide ([C4mim][NTf2]) have been determined at 298.15K and atmospheric pressure. The excess molar volumes as well as molar refraction and viscosity changes of mixing have been calculated and adequately fitted to the Redlich-Kister equation. The adjustable parameters and the standard deviations between experimental and calculated values are reported. Vapour-liquid equilibrium (VLE) data have been obtained for these binary and ternary systems at 101.32. kPa and were adequately correlated by means of NRTL and UNIQUAC equations for the liquid phase activity coefficient. © 2010 Elsevier B.V.